ANALYSIS OF TRANSFER PRICING AS A TAX AVOIDANCE AND PROPOSED SUGGESTION TO PREVENT ITS DISADVANTAGES - Kukuh Leksono S. Aditya (Yuridika, 2015)
It is very obvious that businesses upholding the main economic principal “obtai ning maximum profit by minimum capital/investment”. In this paper’s context, the words “capital/investment”in that principal not only defined as a “pre company’s wealth contribution” but also any company’s wealth which required for running the businesses. Therefore, it is not impossible that undertakings always developing in their own ways to increase their profit by avoiding taxes. Eventhough the tax avoiding is not illegal, in some circumstances it disrupts the goverment’s revenue. Using statutory and case approaches, this paper firstly trying to determine the transfer pricing concept in regards to positive and negative connotations. Secondly, the examination of transfer pricing implementation by undertakings. Then lastly, this paper provides some proposals to prevent the disadvantages of transfer pricing.